Recruitment and Lessons Learned from a Community-Based Intervention Program: The Learning Families Project in Hong Kong - Chu, Joanna T. W.; Wan, Alice; Stewart, Sunita M.; Ng, Kwok Tung; Lam, Tai Hing; Chan, Sophia S. (Frontiers in Public Health, 2018)
Background Recruitment is central to any research project, and recruitment itself should be well documented and researched. We describe our recruitment efforts for a community-based research project—entitled the Learning Families Project—conducted in Hong Kong. Methods In collaboration with community stakeholders, residents from a public housing estate were recruited to participate in family programs aimed at enhancing family well-being. Various recruitment strategies were employed including the distribution of 19,200 leaflets, 688 posters, a banner, a kick-off ceremony, 10 promotion activities, 1,000 direct calls, word of mouth, 51 mobile counters, and 10 door-to-door visits. Drawing on field notes, research logs, short questionnaires, and focus group conducted with our community partners and residents, we describe and discuss our recruitment strategies, challenges, and lessons learned. Results Over a 9-month period, 980 participants were recruited and participated in our study, exceeding our recruitment goal (860 participants). Several observations were made including active recruitment strategies (i.e., door-to-door and mobile counter) being more effective than passive strategies (i.e., posters and leaflets); the importance of raising project awareness to facilitate recruitment; and the challenges encountered (i.e., burn-out and loss of motivation of staff, decreased community capacity in collaborating in research projects). Conclusion The lessons learned include the importance of engaging Chinese communities, utilizing a positive outreach approach, and setting realistic expectations. Although similar recruitment strategies have been reported the West, a number of cultural differences should be taken into account when working with Chinese population. Further research is needed to examine the effectiveness of tailoring recruitment strategies to various populations.